IDENTIFICATION OF RISK OF DECARBONIZATION OF THE OIL AND GAS INDUSTRY - GRYNIUK, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the global greenhouse gas emissions of the oil and gas industry in the value chain; the four scenarios for reducing carbon dioxide emissions developed by the International Energy Agency. The estimated total average annual capital expenditures on low-emissions technologies with synergies for the oil and gas industry were analyzed within the scope of the Net Zero Emission scenario. It was investigated, that the NZE brought significant challenges for oil and gas industry, but it also brought opportunities. The decarbonization measures that can be applied in the oil and gas industry were investigated. The most acceptable decarbonization measures that can be applied by domestic oil and gas companies were examined.Based on the analysis, the risks of decarbonization of the oil and gas industry were investigated and identified. The classification of risks of implementing decarbonization measures (in particular, Carbon capture, use, and storage technology (CCUS)) that can be used by oil and gas enterprises has been developed. The following groups of risks and their corresponding risk factors were highlighted: investment, socio-economic, geological, technical-technological, informational, personal risks. The developed classification can be used in developing decarbonization projects for vertically integrated oil and gas companies, particularly in forming the register of project risks.
Keywords: oil and gas industry; decarbonization; risks; the decarbonization risks; technology of carbon capture; use and storage